1986
DOI: 10.1093/jnci/76.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Stomach and Colorectal Cancers in Puerto Rican-Born Residents of New York City2

Abstract: Colorectal cancer incidence and mortality rates for Puerto Rican-born residents in New York City (PR-NYC) for 1975-79 were about two times those for Puerto Ricans living in Puerto Rico (PR-PR) and one-half to almost two-thirds those for other whites in New York City. From 1958 to 1979, colon cancer mortality rates for PR-NYC increased dramatically (i.e., 212% in males and 54% in females), whereas in PR-PR, male rates increased only slightly and female rates remained constant. For stomach cancer, incidence rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…However, the higher proportion of colon cancer compared to rectal cancer in countries with high agestandardized incidence rates for CRC compared with countries with low rates, 45,46 the proximal shift of tumors associated with the increased incidence of CRC observed in migrant studies, [47][48][49][50] and the proximal shift in CRC associated with the increase in the agestandardized incidence rates for CRC observed in the United States in the last 50 years 51 suggest that the proximal shift of colon cancers with increasing age is probably related to environmental factors. Evidence suggesting an interaction between DNA methylation and environmental factors such as micronutrients, chemotherapeutic agents, and metals allows us to speculate that the proximal shift in the distribution of CRC can be attributed to an altered DNA methylation secondary to environmental exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the higher proportion of colon cancer compared to rectal cancer in countries with high agestandardized incidence rates for CRC compared with countries with low rates, 45,46 the proximal shift of tumors associated with the increased incidence of CRC observed in migrant studies, [47][48][49][50] and the proximal shift in CRC associated with the increase in the agestandardized incidence rates for CRC observed in the United States in the last 50 years 51 suggest that the proximal shift of colon cancers with increasing age is probably related to environmental factors. Evidence suggesting an interaction between DNA methylation and environmental factors such as micronutrients, chemotherapeutic agents, and metals allows us to speculate that the proximal shift in the distribution of CRC can be attributed to an altered DNA methylation secondary to environmental exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Another study analyzed differences in cancer rates between first and second generation migrants relative to the host country and stratified by country of origin showing cancer site-specific patterns for succeeding generations [18]. Results from a study by Warshauer et al [19] indicated increasing rates of colorectal and stomach cancer incidence and mortality of Puerto Rican-born residents after migration to New York City.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of Hispanic immigrants have been limited to those States which have large populations of Hispanics and which collect information concerning Hispanic origin from State cancer registries and/or death certificates. These have included studies of populations which were of primarily Mexican origin in New Mexico (Key, 1981), Colorado (Savitz, 1986), Texas (Martin and Suarez, 1987), and Los Angeles County (Menck et al, 1975;Mack et al, 1985), and studies of Puerto Ricans in New York City (Rosenwaike and Shai, 1986;Warshauer et al, 1986). However, only the Los Angeles and New York studies calculated risks separately for the nonnative-born population.…”
mentioning
confidence: 99%